PENYULUHAN PROSEDUR PENGURUSAN DAN PENTINGNYA LEGALITAS SURAT IZIN USAHA PERDAGANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DIDESA SUNGAI JAMBU KECAMATAN KAYU ARO BARAT - Sarmigi, Elex; Sumanti, Eva; Yani, Ahmad; Nisa, Fitri Agma (Institut Agama Islam Negeri Kerinci, 2023)
Licensing is the most important part in a trading business. Licensing is so important because the existence of a license can determine whether or not a trading business is carried out. Of the many existing permits, one of which is a trading business license. To create a conducive business climate to encourage increased investment, it is necessary to support the implementation of excellent SIUP issuance services to the business world. Issuance of a Trading Business Permit as a business legality in the trade sector, it is necessary to provide convenience, uniformity and order so as to improve the smooth running of public services. For this reason, the Minister of Trade issues regulation Number 36/M-DAG/PER/2007 concerning the Issuance of Trading Business Permits. The purpose of this counseling is to let the public know that in the process of making a business license it is not difficult and also that this trading business license is very important for MSME entrepreneurs. The method of implementing the procedure for managing the trading business license is through socialization and counseling. As a result, people who have MSME businesses understand and understand that the legality of the business is very important and also for entrepreneurs who do not want to take care of the letter.